Integrated Approach to Rising the Level of Social and Economic Development of the Region Based on Tourism: Coordinated Development on Regional, Sectoral and Micro-Levels - S. B. Boldyreva (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
There are various mechanisms of developing tourism on the regional level, which are based on different methods and approaches. The article shows that managing tourism on the region level is carried out within the frames of classic functions of the management theory. At the same time the sectoral level of the coordinated development of tourism is closely related to the regional one and it can be attributed, as well as the regional one, to the mezzo-level of tourism management. In our opinion, it is necessary to distinguish these levels of coordinated development. The need to single out the sectoral level of coordinated development of tourism today is connected with wide proliferation, both in practice and in theory, the ideas of cluster approach to the development of travel industry. To analyze and work out proposals dealing with upgrading mechanisms of managing social and economic development of the region on the basis of tourism on the regional, sectoral and micro-levels it is possible to use the integrated approach.